Blood plasma lipid profile in glial tumors - L. M. Obukhova; E. V. Balavina; T. A. Veselova; I. A. Medyanik; A. S. Grishin; V. F. Lazukin; M. M. Kontorshchikov (Успехи молекулярной онкологии)
Introduction. In glial tumors, lipid metabolism becomes abnormal. Analysis of lipid metabolism components can be an important characteristic of molecular and genetic profile of gliomas.Aim. To determine the correlation between plasma lipidome profile and immunohistochemical characteristics of glial tumors and to evaluate clinical significance of blood lipid spectrum analysis in preoperative assessment of molecular profile of gliomas.Materials and methods. Immunohistochemical measurement of O-6-methylguanine-DNA-methyl transferase (MGMT), Ki-67, p53, IDH1 tumor markers was performed using the corresponding antibody clones. Composition of plasma lipids was assessed using thin layer chromatography.Results. Even at the early stages of gliomagenesis, significant differences in cholesterol ethers, lysophosphatidylcholines, phosphatidylcholine (PC)/ lysophosphatidylcholine (LPC) ratio, neutral lipids (NL)/phospholipids (PL) in the blood were observed. Significant correlations between Ki-67, MGMT tumor markers and the above-mentioned lipidome parameters were found. The PC/LPC, NL/PL ratios in the blood of the patients from the groups with higher (above 10 %) and lower (below 10 %) Ki-67 mitotic indexes compared to healthy individuals were significantly lower. Therefore, the values of lipidome parameters allow to indirectly assess proliferative activity of gliomas which can be used for preoperative diagnosis of these tumors. No significant differences in the plasma PC/LPC and NL/PL ratios were found between the groups with MGMT promoter methylation and without it. No indirect predictor criteria for MGMT were found.Conclusion. It is impossible to determine decreased epigenetic activity of corresponding transcripts and preoperative prognosis for alkylating agent therapy based on the parameters of plasma lipid metabolism.